2020
DOI: 10.3390/biom10030451
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Compounds from Lespedeza Bicolor Root Bark Inhibit Progression of Human Prostate Cancer Cells via Induction of Apoptosis and Cell Cycle Arrest

Abstract: From a root bark of Lespedeza bicolor Turch we isolated two new (7 and 8) and six previously known compounds (1-6) belonging to the group of prenylated polyphenols. Their structures were elucidated using mass spectrometry, nuclear magnetic resonance and circular dichroism spectroscopy. These natural compounds selectively inhibited human drug-resistant prostate cancer in vitro. Prenylated pterocarpans 1-3 prevented the cell cycle progression of human cancer cells in S-phase. This was accompanied by a reduced ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Catechin, genistein daidzein, luteolin, naringenin, and rutin were identified in the powdered extract of L. bicolor . The root extracts contain polyphenolic compounds that delay prostate cancer progression ( Dyshlovoy et al, 2020 ). Also, the effects of L. bicolor on cognitive function were investigated in a mice model of AD using a cerebral injection of Aβ.…”
Section: Estrogenic Plants and Compounds With Potential Effects Against Alzheimer's Diseasementioning
confidence: 99%
“…Catechin, genistein daidzein, luteolin, naringenin, and rutin were identified in the powdered extract of L. bicolor . The root extracts contain polyphenolic compounds that delay prostate cancer progression ( Dyshlovoy et al, 2020 ). Also, the effects of L. bicolor on cognitive function were investigated in a mice model of AD using a cerebral injection of Aβ.…”
Section: Estrogenic Plants and Compounds With Potential Effects Against Alzheimer's Diseasementioning
confidence: 99%
“…Polyphenolic compounds isolated from Lespedeza bicolour root bark extract induced sub-G1 cell cycle arrest in human drug-resistant prostate cancer cell line PC-3. 44 Cells infected with pathogens generate reactive oxygen species (ROS) such as peroxides, hydroxyl radicals, and superoxides to fight the infection. Likewise, ROS is also produced in retaliation to certain medications; on a similar basis, antiprotozoal drugs execute parasites in infected cells.…”
Section: Discussionmentioning
confidence: 99%
“…There is consensus that polyphenols act as anti-cancer agents by reducing cell growth, arresting cell cycle and inducing apoptosis ( Rajamani 2018 ; Chaves et al, 2020 ; Dyshlovoy et al, 2020 ). In a previous work, our group showed that YMe, which contains a complex mixture of phytochemicals, reduces cell growth and induces apoptosis due to an activation of the intrinsic pathway in a colorectal cancer model.…”
Section: Discussionmentioning
confidence: 99%